(untitled) (Heritage, 2024)
It is known to the scientific, professional and lay public that the United States of America, after the terrorist act of September 11, 2001, which was carried out on its territory, designated Osama Bin Laden and Al Qaeda as the culprit. The subject of research in this paper is the financing of terrorism from the territory of the United States of America. The aim of the work is to provide reasoned, objective and systematized findings on the support of terrorist financing on the territory of the USA, through the activities of charitable organizations that collected money on its territory. Almost all basic analytical and synthetic methods of knowledge were applied in the preparation of the work, with an emphasis on analysis, synthesis, generalization and the inductive-deductive method. From the corpus of general scientific methods, the general scientific statistical and hypothetical-deductive method was applied in the research of the topic, and from the group of methods for data collection, the method of content analysis of available documents was used, that is, its technique of qualitative analysis of documents. Two results emerged from the research. One, which indicates that in the decades before the terrorist attacks of September 11, 2001, Islamic charities in the United States developed donor networks, perfected techniques and covertly aided and financed terrorist groups and individuals, often with the tacit approval of American security organizations. Second, that just a few days after the terrorist attacks carried out on September 11, 2001, the President of the United States of America, with Executive Order 13224, designated a number of Islamic charitable organizations in the United States that covertly worked, supported and financed terrorism with funds collected from American citizens and organization.